Factors affecting sexting behaviours among young adults in Malaysia - Seah, Adeline Wei Xuan; Lee, Xin Lin; Lim, Shar Min (2020)
In recent years, the phenomenon of sexting has received tremendous attention by the researchers as several negative consequences were found attributed to sexting. However, such phenomenon is not well-understood in Malaysia context because so far only one local qualitative study was dedicated to understand this behaviour among a group of teenagers. Thus, the present study decided to further investigate on this topic by adopting quantitative, cross-sectional and correlational research design. Particularly, this study intended to examine sexting prevalence rate among Malaysian young adults; gender and relationship status differences in sexting behaviour; as well as the factors (self-esteem, sexual sensation seeking and perceived peer pressure) that would affect people to sext. Hence, a total of 396 Malaysian young adults (aged 18 to 38 years old, M = 24.21, SD = 3.15) were recruited by using purposive sampling method and online survey serves as a tool for data collection. Based on the findings of this study, 72.5% of the participants do engaged in sexting and no significant gender difference was found in sexting behaviour. As for relationship status, individuals in a relationship sext more than the singles, but no significant difference was found in married individuals. Moreover, findings also indicated that only sexual sensation seeking significantly predicts sexting behaviour, while self-esteem was not associated with sexting. Therefore, the findings in this study could enrich the literature of sexual media studies in Malaysia, and provide useful data for future researchers to investigate on this topic.